Selenium, Vitamin C and N-Acetylcysteine do not Reduce the Risk of Acute Kidney Injury after Off-Pump CABG: a Randomized Clinical Trial - Shahram Amini; Hojat Naghavi Robabi; Mohammad Abbasi Tashnizi; Vida Vakili (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The aim of this study was to investigate the impact of perioperative administration of N-acetylcysteine, selenium and vitamin C on the incidence and outcomes of acute kidney injury after off-pump coronary bypass graft surgery. Methods: 291 patients requiring elective off-pump coronary bypass graft surgery were randomized to receive either N-acetylcysteine, vitamin C and selenium 600 mg, 1500 mg, 0.5 mg, and nothing orally twice a day, respectively, from the day before to 2 days after surgery. They were assessed for the development of acute kidney injury using Acute Kidney Injury Network criteria, time of onset, its severity and duration, duration of mechanical ventilation, intensive care unit and hospital length of stay, and in-hospital mortality. Results: 272 patients completed the study. The total incidence of acute kidney injury was 22.1% (n=60) with 14 (20.9%), 15 (22.1%), 21 (31.8%), and 10 (14.1%) patients in the vitamin C, NAC, selenium, and control groups, respectively (P=0.096). We did not register significant differences in the incidence, the time of occurrence, the severity and the duration of acute kidney injury, as well as the duration of mechanical ventilation, the intensive care unit and hospital length of stay, and the in-hospital mortality among the four groups. Conclusion: We found that perioperative administration of N-acetylcysteine, vitamin C and selenium were not effective in preventing acute kidney injury and associated morbidity and mortality after off-pump coronary bypass graft surgery.